2017
DOI: 10.3354/meps12245
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting ecological impacts of native and non‑native marine crabs: a global meta-analysis

Abstract: Crab species Carapace width (mm) Source Acanthocyclus gayi 24.0 Garth (1957) Acanthocyclus hassleri 25.0 Rathbun (1930) Achelous spinimanus 110.0 Williams (1984) Callinectes sapidus 168.0 Williams (1984) Cancer antennarius 118.0 Rathbun (1930) Cancer borealis 143.0 Williams (1984) Cancer irroratus 119.0 Williams (1984 Cancer pagurus 130.0 Ingle (1997) Cancer productus 157.5 Rathbun (1930) Caphyra rotundifrons 13.0 Jenkins (2012) Carcinus aestuarii 65.0 sealifebase.org Carcinus maenas 79.4 Rathbun (1930) Cyclog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 70 publications
4
8
0
Order By: Relevance
“…Since lobsters' response to both green crab and rock crab was similar, it demonstrated impacts on lobster catch were not specific to green crab but were rather due to the presence of either crab species in the traps. This finding aligns with those of Howard, Therriault & Côté (2017) which found non-native crabs did not reduce prey abundance via direct consumption any more than native crabs. Howard, Therriault & Côté (2017) also reported on the paucity of studies that directly compared impacts of native versus non-native species.…”
Section: Procedural Controlsupporting
confidence: 91%
See 1 more Smart Citation
“…Since lobsters' response to both green crab and rock crab was similar, it demonstrated impacts on lobster catch were not specific to green crab but were rather due to the presence of either crab species in the traps. This finding aligns with those of Howard, Therriault & Côté (2017) which found non-native crabs did not reduce prey abundance via direct consumption any more than native crabs. Howard, Therriault & Côté (2017) also reported on the paucity of studies that directly compared impacts of native versus non-native species.…”
Section: Procedural Controlsupporting
confidence: 91%
“…This finding aligns with those of Howard, Therriault & Côté (2017) which found non-native crabs did not reduce prey abundance via direct consumption any more than native crabs. Howard, Therriault & Côté (2017) also reported on the paucity of studies that directly compared impacts of native versus non-native species. Had we not incorporated a procedural control, our conclusion would likely have been that green crab caused declines in trap effectiveness, with the implication that something about their identity as an invader was the root cause.…”
Section: Procedural Controlsupporting
confidence: 91%
“…Since lobsters' response to both green crab and rock crab was similar, it demonstrated impacts on lobster catch were not specific to green crab but were rather due to the presence of either crab species in the traps. This finding aligns with those of Howard et al, (2017) which found non-native crabs did not reduce prey abundance via direct consumption any more than native crabs. Howard et al, (2017) also reported on the paucity of studies that directly compared impacts of native versus non-native species.…”
Section: Procedural Controlsupporting
confidence: 91%
“…This finding aligns with those of Howard et al, (2017) which found non-native crabs did not reduce prey abundance via direct consumption any more than native crabs. Howard et al, (2017) also reported on the paucity of studies that directly compared impacts of native versus non-native species. Had we not incorporated a procedural control, our conclusion would likely have been that green crab caused declines in trap effectiveness, with the implication that something about their identity as an invader was the root cause.…”
Section: Procedural Controlsupporting
confidence: 91%
“…In this respect, meta-analyses employing quantitative methods are conceivably more objective than review articles, because they should be less susceptible to preconceived notions. Although some meta-analyses concluded that the impacts of NIS are stronger and/ or more detrimental than those of indigenous species (Ferlian et al, 2018;Paolucci, MacIsaac, & Ricciardi, 2013;Salo, Korpimaki, Banks, Nordstrom, & Dickman, 2007;Simberloff, Souza, Nuñez, Barrios-Garcia, & Bunn, 2012;van Hengstum, Hooftman, Oostermeijer, Tienderen, & Mack, 2014;Vilá et al, 2011;Wood et al, 2017;Yoon & Read, 2016), many suggested positive influences and/or that the purported negative effects of NIS are not supported by evidence (Charlebois, Sargent, & Maherali, 2017;Gurevitch & Padilla, 2004;Norkko et al, 2011;Pintor, Byers, & Anderson, 2015;Radville, Gonda-King, Gómez, Kaplan, & Preisser Evan, 2014;Reise, Olenin, & Thieltges, 2006), and most found variable and context-dependent impacts (Cameron, Vilà, Cabeza, & Sykes, 2016;Guy-Haim et al, 2018;Higgins & Vander Zanden, 2010;Howard, Therriault, & Côté, 2017;Martin, Newton, & Bullock, 2017;Nelson et al, 2017;Potgieter et al, 2017;Pysek et al, 2008;Qiu, 2015;Thomsen et al, 2014;Twardochleb, Olden, & Larson, 2013;Vaz et al, 2018;Ward & Ricciardi, 2007), thus hindering broad generalizations.…”
Section: Interpre Ting and Recon Ciling D Iss Entmentioning
confidence: 99%